A região de Araraquara e a constituição do local: experiência em desenvolvimento rural a partir do SAI - Sistema Agroindustrial Integrado - Campos, Ricardo Luiz Sapia de [UNESP] (My University, 2011)
The research aims to map and understand the SAI- Integrated Agroindustrial System of SEBRAE, topic program directed to small and medium "rural entrepreneurs". The SAI policy seeks targeted result saiming to qualify productive agents (smallholders) to a "mark et under construction". In the study I high light the "production location", as a constituent en vironment with own productive and defining characteristics of this location and of the productive agent. I aim to perceive the location (region of Araraquara) as a topic en vironment of a type of "alternative "agriculture, that in principle is “parallel” to the large hegemonic model of the economies of scale, of monoculture and concentrative, which in the region is taken as that of the "sugarcane industry". I understand the coexistence of these different models as central to understand the development of capitalism, which I treat as "cognitive capitalism".

A pesquisa busca mapear e entender o SAI - Sistema Agroindustrial Integrado do SEBRAE, programa tópico direcionado á pequenos e médios “empreendedores rurais”. A política do SAI busca resultados direcionados objetivando qualificar os agentes produtivos (pequenos proprietários) para um “mercado em construção”. Destaco no estudo o “local da produção”, como ambiente constituinte apresentando características produtivas próprias e definidoras deste local e do agente produtivo. Busco entender o local (região de Araraquara) como ambiente tópico de um tipo de agricultura “alternativa”, e que em principio é “paralela” ao grande modelo hegemônico de economia de escala, monocultora e concentradora, que na região é lida como sendo aquela da “indústria canavieira”. Entendo a coexistência destes diferentes modelos como centrais para entender o desenvolvimento do capitalismo, e que trato como “capitalismo cognitivo”.
The region of araraquara and the local formation: experience in rural development from SAI (Integrated Agroindustrial System)
Keywords: Cognitive capitalism; Rural development; Productive agents; Production territory and local development; Capitalismo cognitivo; Desenvolvimento rural; Agentes produtivos; Território da produção e desenvolvimento local